Sosialisasi Tentang Perawatan Luka Perineum Pada Ibu Nifas di Klinik Murniati - Putri, Maidina; Pratiwi, Debby; Hayati, Suka; Rahma, Siti (Cattleya Darmaya Fortuna, 2022)
In 2015, there were 2.7 million cases of perineal wounds in women giving birth in the world, where this figure is expected to reach 6.3 million in 2050. In Asia, the problem of perineal tears is quite common in society, 50% of the world's perineal tears occur. In Asia, the prevalence of mothers experiencing perineal tears in Indonesia in the 25-30 year age group is 24%, and in mothers aged 32-39 years it is 62% (World Health Organization, 2015). Perineal care is the fulfillment of the need to nourish the area between the thighs bordered by the vulva and anus in mothers during the period between the birth of the placenta and the return of the genital organs to their pre-pregnancy state (Morison, 2019). Special perineal care for women after childbirth reduces discomfort, prevents infection, and promotes healing. Provides comfort to mothers, improves maternal health, reduces maternal mortality due to incorrect wound care (Ariyanti, 2020).